Financial Conditions and Corporate Governances on Sustainability Report Disclosure - Rahmawati Evi; Nugroho Mochammad Aditya; Kholid Arif Wahyu Nur (SHS Web of Conferences)
Sustainability reporting is necessary for a company to disclose because it is a form of accountability in supporting its sustainable goals. Thus, this study aims to determine the financial condition factor and Good Corporate Governance on Sustainability Report Disclosure controlled by the COVID-19 pandemic. The population of this study is companies from Indonesia that were finalists of the Asia Sustainability Reporting Awards (ASRA) 2022 and published annual reports and sustainability reports in 2018-2022. The sample selection in this study employed purposive sampling to acquire a sample based on preset criteria. This study is classified as quantitative research, specifically utilizing secondary data. This study employs balanced panel regression to analyze the data. The study used the Common Effect Model (CEM) as the estimation model. This research reveals that liquidity, firm size, and the COVID-19 pandemic positively affect sustainability report disclosure. On the other hand, profitability, board of commissioners, and the audit committee do not affect sustainability report disclosure.